Postresuscitative Brain Tissue Blood Flow in Animals That Have Experienced Clinical Death - A. V. Budayev (Общая реаниматология, 2006)
The general mechanisms and specific features of recovery of postresuscitative cerebral and systemic hemodynamics were studied in the animals that had experienced clinical death caused by various factors that were components of severe injuries during technogenic catastrophes (blood loss, carbon monoxide intoxication, chest compression). The hydrogen clearance method was used to record tissue blood flow. The thermodilution technique was employed to estimate cardiac output. There was a close, direct correlation of postresuscitative cerebral circulatory changes with the phasic pattern of recovery of cardiac output and its redistribution. An initial short increase in cerebral hemoperfusion occurred with higher cardiac output (a hyperperfusion phase) and its supradiaphragmatic fraction (an early postresuscitative circulatory centralization reaction). There was a further decrease with a progressive reduction in cardiac output and its supradiaphragmatic fraction. Postresuscitative cerebral hyperperfusion was shown to have the adaptive range favorable for vital function recovery processes and ultimate resuscitative Results. All things considered, the possibility exists of artificially modifying the postresuscitative range of cerebral hyperperfusion, by controlling the distribution of cardiac output.